2012
DOI: 10.1155/2012/768126
|View full text |Cite
|
Sign up to set email alerts
|

A Nanomechanical Investigation of Three Putative Anti-Erosion Agents: Remineralisation and Protection against Demineralisation

Abstract: An increasing interest in dental erosion as a clinical and scientific phenomenon has led to concerted efforts to identify agents which might protect against erosion. In this study, nanoindentation was used to investigate inhibition of erosive enamel demineralisation over time scales with direct clinical relevance. Nanohardness of polished human enamel specimens (n = 8 per group) was measured at baseline (B), after demineralisation (D1: citric acid, 0.3% w/v, pH3.20, 20s), after treatment (T), and after a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…An increased interest in dental erosion as a clinical phenomenon has led to efforts to identify agents that are efficient in protecting dental hard tissues against chemical dissolution by nonbacterial acids [Abdulah et al, 2012]. In erosive lesions, the demineralized layer is limited to the surface area [Lussi and Carvalho, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…An increased interest in dental erosion as a clinical phenomenon has led to efforts to identify agents that are efficient in protecting dental hard tissues against chemical dissolution by nonbacterial acids [Abdulah et al, 2012]. In erosive lesions, the demineralized layer is limited to the surface area [Lussi and Carvalho, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…9,[12][13][14] This process has been tracked by atomic force microscopy (AFM), 15 attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) 16 and nanoindentation experiments. [17][18][19][20][21] The effect of calcium-phosphate-loaded casein (calcium -5 -phosphopeptide (CCP) and amorphous calcium phosphate (ACP) nanoclusters. 9,24,37 Taking into account that the presence of saliva has a remarkable influence on the REM process due to its buffer properties and its natural content of calcium and phosphate ions, 38,39 the demineralized human tooth slices were treated with a mixture of Tooth Mousse paste and native saliva.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of studies regarding the demineralization of dental hard tissue, dentine, and enamel, by acids and acidic drinks; these studies have shown that the tooth surface becomes rough as a result of minerals being leached out. , This process has been tracked by atomic force microscopy (AFM), attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR), and nanoindentation experiments. The effect of calcium-phosphate-loaded casein (calcium phosphopeptide-amorphous calcium phosphate, CPP-ACP complex) on affected tooth surfaces has also been studied. The complex was shown to reduce the surface roughness of eroded dentine and enamel samples , and to reduce dentine hypersensitivities. The application of the CPP-ACP complex combined with clinical tooth bleaching processes or the application together with self-etching bonding agents resulted in less erosion of the enamel surfaces but also in reduced microshear bond strengths . Furthermore, the paste is known to inhibit the growth of bacterial biofilms of Streptococcus mutans as well as fibroblasts on the tooth surface. , …”
Section: Introductionmentioning
confidence: 99%
“…Esses fatores contribuem para que sejam estabelecidas diferentes conclusões, com achados promissores (REES et al, 2007;RANJITKAR et al, 2009a;RANJITKAR et al, 2009b;POGGIO et al, 2009;MANTON et al, 2009;PRESTES et al, 2013, ALENCAR et al, 2014) ou desestimuladores (WANG et al, 2011WEGEHAUPT et al, 2012;ABDULLAH et al, 2012;ATTIN, 2014) (HARA et al, 2006). Desse modo, a desmineralização da superfície dentária ocorrerá somente após a difusão dos ácidos pela película ou após a sua dissolução parcial e remoção decorrente da interação com o ácido, o que determina que, apesar de não prevenir o contato direto do ácido com a superficie dentária, a pelicula adquirida pode reduzir ou retardar essa interação imediata.…”
Section: Considerações Sobre Os Resultadosunclassified
“…Diferentes veículos para o CPP-ACP têm sido avaliados no que se refere à prevenção da erosão dentária (GUPTA; PRAKASH, 2011), a exemplo do emprego de pasta ou mousse de aplicação tópica (REES;LOYN;CHADWICK, 2007;RANJITKAR et al, 2009a;RANJITKAR et al, 2009b;POGGIO et al, 2009;WANG et al, 2011;ABDULLAH et al, 2012;WEGEHAUPT et al, 2012;POGGIO et al, 2013;ATTIN, 2014) ou do acréscimo do CPP-ACP à bebida erosiva (RAMALINGAM et al, 2005;MANTON et al, 2010). Independentemente do veículo, alguns estudos encontraram proteção parcial (RAMALINGAM et al, 2005;REES;LOYN;CHADWICK, 2007;POGGIO et al, 2009;POGGIO et al, 2013;MANTON et al, 2010) ou nenhum efeito (WANG et al, 2011;ABDULLAH et al, 2012;WEGEHAUPT et al, 2012) do CPP-ACP contra a erosão dentária. Outros estudos mostraram um efeito protetor até mesmo em condições erosivas severas (RANJITKAR et al, 2009a, RANJITKAR et al, 2009b, RANJITKAR et al, 2009c, supostamente em função da remineralização pelo depósito de mineral na zona de superfície porosa do esmalte erodido (TANTBIROJN et al, 2008).…”
Section: Lista De Abreviaturas Siglas Símbolos E Palavras Deunclassified